The Effect of Product Quality, Brand Image, Brand Trust, and Word of Mouth on Customer Loyalty of Garnier Facial Wash Products on National University Students - Rusydina Ghaisani; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product quality, Brand Image, Brand Trust, and Word of Mouth on Customer Loyalty for Garnier facial wash products among national university students. The sample in this study were 100 national university student respondents who used Garnier facial wash products. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service solution (SPSS) version 26.0 program. From the results of multiple linear regression analysis, using the t test where Product Quality (X1) has a positive and significant effect on Customer Loyalty (Y), Brand image (X2) has a positive and significant effect on Customer Loyalty (Y), Brand Trust (X3) has an effect positive and significant impact on Customer Loyalty (Y), Word Of Mouth (X4) has a positive and significant effect on Customer Loyalty (Y). So it can be concluded that Product Quality, Brand Image, Brand Trust, and Word Of Mouth have a positive and significant effect on Customer Loyalty.